2007
DOI: 10.1021/nl071190f
|View full text |Cite
|
Sign up to set email alerts
|

GaAs:Mn Nanowires Grown by Molecular Beam Epitaxy of (Ga,Mn)As at MnAs Segregation Conditions

Abstract: ABSTRACT:GaAs:Mn nanowires were obtained on GaAs(001) and GaAs(111)B substrates by molecular beam epitaxial growth of (Ga,Mn)As at conditions leading to MnAs phase separation. Their density is proportional to the density of catalyzing MnAs nanoislands, which can be controlled by the Mn flux and/or the substrate temperature. After deposition corresponding to a 200 nm thick (Ga,Mn)As layer the nanowires are around 700 nm long. Their shapes are tapered, with typical diameters around 30 nm at the base and 7 nm at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 31 publications
(63 reference statements)
0
64
1
Order By: Relevance
“…Although the growth of monocrystalline GaMnAs layers using a high Mn flux is impossible at high temperatures, 11 1-D nanowire (NW) growth at a Mn/Ga flux ratio of several percent is possible, which has been demonstrated in several studies. [11][12][13][14] Although some studies have shown room temperature ferromagnetism, 14,15 the origin and mechanism of the reported magnetization are not clear.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the growth of monocrystalline GaMnAs layers using a high Mn flux is impossible at high temperatures, 11 1-D nanowire (NW) growth at a Mn/Ga flux ratio of several percent is possible, which has been demonstrated in several studies. [11][12][13][14] Although some studies have shown room temperature ferromagnetism, 14,15 the origin and mechanism of the reported magnetization are not clear.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Although some studies have shown room temperature ferromagnetism, 14,15 the origin and mechanism of the reported magnetization are not clear. For example, the formation of ferromagnetic precipitates or clusters such as MnAs should be considered as a possible source of magnetism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We note that in previous studies the growth of GaMnAs nanowires under typical NW, i.e., high temperature conditions, has been reported. [28][29][30] Sadowski et al 29 showed that the growth of GaMnAs at MnAs segregation conditions led to the formation of MnAs nanocluster acting as catalyst for the NW growth. The obtained NWs were strongly tapered with side branches.…”
mentioning
confidence: 99%